Transient window of resilience during early development minimizes teratogenic effects of heat in zebrafish embryos. Issue 8 (11th August 2018) - Menon, Triveni; Nair, Sreelaja
Abstract : Background: Transient heat shock during early development is an established experimental paradigm for doubling the genome of the zebrafish zygote, which has practical applications in expedited identification of recessive mutations in genetic screens. Despite the simplicity of the strategy and the genetic tractability of zebrafish, heat shock has not been used for genome doubling since the proof‐of‐principle experiments done in the 1980s. This is because of poor survival of embryos that ensue from transient heat shocks and gross developmental abnormalities in the few survivors, which is incompatible with phenotype driven screens.Results: We show that heat shocks during early zebrafish development uncouple the second cycle of DNA and centrosome duplication. Interestingly, the developmental time of the heat shock that triggers the dissociation between DNA and centrosome duplication cycles significantly affect the potential of embryos to survive and attain normal morphology. The potential to develop normally after a heat shock alters in a developmental time span of 2 min in zebrafish embryos, a phenomenon that has not been reported in any species.Conclusions: The existence of heat resilient developmental windows and reduced heat teratogenicity during these windows could be an effective step forward in practical application of transient heat for experimental manipulation of ploidy in zebrafish. More broadly, heat resilience before zygotic genome activation suggests that metazoan embryos may possess innate protective features against heat beyond the canonical heat shock response. Developmental Dynamics 247:992–1004, 2018 . © 2018 Wiley Periodicals, Inc. Key Findings: Zebrafish embryos at the end of pronuclear fusion and before initiation of zygotic mitosis are resistant to teratogenic effects of heat. The teratogenic heat resilient window exists transiently during the maternally controlled phase of development. Heat shock during the teratogenic heat resilient window enables generation of morphologically normal zebrafish tetraploids. Diploidization of haploids by transient heat shocks during the teratogenic heat resilient windows aids in effective generation of gynogenic diploids.